A RED modified weighted moving average for soft real-time application - Domańska, Joanna; Domański, Adam; Augustyn, Dariusz R.; Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
The popularity of TCP/IP has resulted in an increase in usage of best-effort networks for real-time communication. Much effort has been spent to ensure quality of service for soft real-time traffic over IP networks. The Internet Engineering Task Force has proposed some architecture components, such as Active Queue Management (AQM). The paper investigates the influence of the weighted moving average on packet waiting time reduction for an AQM mechanism: the RED algorithm.
Keywords: active queue management; soft real-time; dropping packets